Continuous Bioethanol Production Using Uncontrolled Process in a Laboratory Scale of Integrated Aerobic-Anaerobic Baffled Reactor - Margono, Margono; Kaavessina, Mujtahid; Mior Ahmad Khushairi, Mohd Zahari; Anwaruddin, Hisyam (Budapest University of Technology and Economics, 2020)
The expensiveness of bioethanol has made it unattractive and uncompetitive for alternative energy sources. Therefore, several ways to reduce the production cost of bioethanol become interesting topics, e.g. increasing its productivity. This research investigated the performance sensitivity of a laboratory scale of integrated aerobic-anaerobic baffled reactor (IAABR) towards the residence time. The ethanol productivity was monitored to know the optimum residence time. The difference residence times were varied between at 19.2 h and 26.7 h by using difference volume of fermenters i.e. 10 and 100 l, respectively. Molasses as a medium was fed into a reactor containing one compartment of aerobic fermentation and three compartments of anaerobic fermentation. Total sugar and bioethanol concentration were measured for each compartment to determine the production yield to sugar consumption and bioethanol productivity. The fermentation process was conducted at 30 °C, medium pH (4-5), and feed sugar concentration of 170 g/l. The results showed that the optimum residence time in this investigation range is 19.2 h. The ethanol productivity was recorded at 4.63 g/l.h and the production yield to sugar was obtained at 46 % (equivalent to 86 % of theoretical yield) with average feeding of molasses at 0.52 l/h.